PENGEMBANGAN LKPD BERBASIS SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY MATERI LARUTAN PENYANGGA DI SMAN 1 SUNGAI RAYA - Pinta Rini Harpiyani; Masriani Masriani; Rahmat Rasmawan (Universitas Tanjungpura, Prodi Pendidikan Kimia, 2021)
AbstractThis study aims was to produce student worksheets based on science, environment, technology and society which are developed based on the results of expert assessments and students' responses based on the results of field trials. This form of research and development (R&D) adopts the ADDIE development model. The subjects of this study were student worksheets based science, environment, technology and society that was tested on class XII MIA students at SMAN 1 Sungai Raya. Data collection instruments used were the validation sheets and students response questionnaires on the product developed. The result of the expert validation (expert judgement) obtained that the interpretation is very proper in terms of aspects of content advisability, presentation advisability, linguistic advisability, and graphic advisability with consecutive total scores of 89.7%, 92.7%, 92.7%, and 87.3% respectively. The results of the student’s responses in initial field trials of 88.4% with very high category and in main field trials of 89.7% in very high category. Keyword : Student Worksheets, SETS Based, Buffer Solution, Feasibility, Student’s Response.